Larval zebrafish as a model for studying individual variability in translational neuroscience research - Jacobs, Elina A. K.; Ryu, Soojin (Frontiers in Behavioral Neuroscience, 2023)
The larval zebrafish is a popular model for translational research into neurological and psychiatric disorders due to its conserved vertebrate brain structures, ease of genetic and experimental manipulation and small size and scalability to large numbers. The possibility of obtaining in-vivo whole-brain cellular resolution neural data is contributing important advances into our understanding of neural circuit function and their relation to behaviour. Here we argue that the larval zebrafish is ideally poised to push our understanding of how neural circuit function relates to behaviour to the next level by including considerations of individual differences. Understanding variability across individuals is particularly relevant for tackling the variable presentations that neuropsychiatric conditions frequently show, and it is equally elemental if we are to achieve personalised medicine in the future. We provide a blueprint for investigating variability by covering examples from humans and other model organisms as well as existing examples from larval zebrafish. We highlight recent studies where variability may be hiding in plain sight and suggest how future studies can take advantage of existing paradigms for further exploring individual variability. We conclude with an outlook on how the field can harness the unique strengths of the zebrafish model to advance this important impending translational question.